Some Notes on Linguistic Politeness and Its Relation to Second Language Teaching - I Ketut Seken (Universitas Pendidikan Ganesha, 2011)
Linguists’ interest in pragmatics is growing fast as the result of a major shift of attention to language as behavior. This growth should bring about awareness among second language teaching practitioners of the importance of incorporating pragmatic skills in all venues of their teaching. Linguistic politeness is one major area of concern in pragmatics and one that has much been thought of as being directly relevant to people’s communicative behaviors in social interaction. As second language teaching is meant to help learners acquire the competence to use the target language in real communication, this competence should enbed, among others, pragmatic abilities, which enable them to use the language appropriately politely. Second language learners need to be socialized and sensitized to politeness tactics and strategies in the target language because to be able to communicate well in the target language they have to master the tactics and strategies of politeness in that language. It is hardly enough that second language teachers only engage them in learning the structure and vocabulary of the target language without giving them competence in using the language to communicate naturally by applying politeness norms appropriate to the interactional situation.